The influence of recovery management post exercise on leg muscle power in extracurricular students basketball - Rangga Divario Prabowo; Prisca Widiawati; Muhammad Putra Ramadhan (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2025)
This study aims to analyze the Influence of post exercise recovery management after training on increasing leg muscle power in extracurricular basketball students. This research method uses One-Group Pre-test Post-test Design with an experimental design research design using a quantitative descriptive research approach. The sampling technique uses total sampling of athletes who participated in the DBL (Developmental Basketball League) competition totaling 24 students consisting of 12 boys and 12 girls. The instrument used in this study was the measurement of leg muscle power using the MD jump test tool. From the results of the study and discussion, it can be concluded that the leg muscle power test using the MD jump test shows that female students get a significant value (p value = 0.031) while male students get a significant value (p value = 0.015). So it can be concluded that this study has a significant effect in recovery using the post exercise recovery management method on the leg muscle power of the female and male teams at SMAN 8 Malang City.